Conhecimento dos profissionais de enfermagem sobre o Projeto Hospitais Sentinela em um hospital do interior paulista - Spadoti, Ariadne [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This study aimed to assess knowledge of nursing professionals (nurses, technicians and nursing assistants) on the Project Sentinel Hospitals in a state hospital in the interior of and identify the occurrence of under-reporting of hospital products and the reasons that prevented the team to notify them. This is a study of a descriptive and exploratory, held in a public hospital in the interior of which serves only patients of the Unified Health System (SUS). The study sample consisted of 245 nurses. Data analysis revealed that the majority of nurses and nursing assistants refers knowledge about Project Sentinel Hospitals. In relation to the Practical nurses less than half know Hospitals Project Sentry. Knowledge of the four spheres of Hospitals Project Sentinel is higher among nurses. Among the practical nurses and nursing assistants prevailing knowledge in the area of Pharmacovigilance. The nurses have more knowledge about the process of notification and are major notifiers. Technicians and nursing assistants are those who have greater interest in learning content as a whole Hospitals Project Sentry. The nurses were the professionals who witnessed the most under-and under-reporting associated with the fear, lack of knowledge on the subject, insecurity and lack of time. It can be concluded that the study identified the knowledge of nurses on Project Sentinel Hospitals and the procedure for notification of technical defects and adverse events related to health products as well as identify the presence of under-reporting among professionals. In addition, the study shows the importance and need for greater disclosure of the activities developed by Project Sentinel Hospitals among nursing professionals through meetings, lectures, brochures, among other outlets

O presente trabalho teve como objetivos avaliar o conhecimento dos profissionais de enfermagem (Enfermeiros, Técnicos e Auxiliares de enfermagem) sobre o Projeto Hospitais Sentinela em um hospital estadual do interior paulista e identificar a ocorrência de sub-notificação de produtos hospitalares bem como os motivos que impediram a equipe de notificá-las. Trata-se de um estudo do tipo descritivo e exploratório, realizado em um Hospital Estadual do interior paulista que atende exclusivamente pacientes do Sistema Único de Saúde (SUS). A amostra do estudo foi constituída por 245 profissionais de enfermagem. A análise dos dados revelou que a maioria dos enfermeiros e auxiliares de enfermagem refere conhecimento sobre o Projeto Hospitais Sentinela. Já em relação aos Técnicos de enfermagem menos da metade conhece o Projeto Hospitais Sentinela. O conhecimento das quatro esferas de atuação do Projeto Hospitais Sentinela é maior entre os enfermeiros. Entre os técnicos de enfermagem e auxiliares de enfermagem prevalecem o conhecimento na área de Farmacovigilância. Os Enfermeiros possuem maior conhecimento a respeito do processo de notificação e são os maiores notificadores. Os técnicos e os auxiliares de enfermagem são os que possuem maior interesse na aprendizagem do conteúdo como um todo do Projeto Hospitais Sentinela. Os enfermeiros foram os profissionais que mais presenciaram a sub-notificação e associaram a com medo, falta de conhecimento sobre o assunto, insegurança e falta de tempo. Pode-se concluir que o estudo permitiu identificar o conhecimento dos profissionais de enfermagem sobre o Projeto Hospitais Sentinela e o seu processo de notificação de queixas técnicas e eventos adversos relacionados aos produtos de saúde bem como identificar a presença de sub-notificação entre os profissionais. Além disso, o trabalho evidencia a importância e a necessidade... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Enfermagem medico-cirurgica; Medicamentos; Pessoal da area médica